Bioaccumulation of human pharmaceuticals in fish across habitats of a tidally influenced urban bayou. (20th November 2015) - Du, Bowen; Haddad, Samuel P.; Luek, Andreas; Scott, W. Casan; Saari, Gavin N.; Burket, S. Rebekah; Breed, Christopher S.; Kelly, Martin; Broach, Linda; Rasmussen, Joseph B.; Chambliss, C. Kevin; Brooks, Bryan W.
Abstract: Though pharmaceuticals and other contaminants of emerging concern are increasingly observed in inland water bodies, the occurrence and bioaccumulation of pharmaceuticals in estuaries and coastal ecosystems are poorly understood. In the present study, bioaccumulation of select pharmaceuticals and other contaminants of emerging concern was examined in fish from Buffalo Bayou, a tidally influenced urban ecosystem that receives effluent from a major (∼200 million gallons per day) municipal wastewater treatment plant in Houston, Texas, USA. Using isotope dilution liquid chromatography–tandem mass spectrometry, various target analytes were observed in effluent, surface water, and multiple fish species. The trophic position of each species was determined using stable isotope analysis. Fish tissue levels of diphenhydramine, which represented the only pharmaceutical detected in all fish species, did not significantly differ between freshwater and marine fish predominantly inhabiting benthic habitats; however, saltwater fish with pelagic habitat preferences significantly accumulated diphenhydramine to the highest levels observed in the present study. Consistent with previous observations from an effluent‐dependent freshwater river, diphenhydramine did not display trophic magnification, which suggests site‐specific, pH‐influenced inhalational uptake to a greater extent than dietary exposure in this tidally influenced urban ecosystem. The findings highlight the importance of understanding differential bioaccumulation and risks of ionizable contaminants of emerging concern in habitats of urbanizing coastal systems. Environ Toxicol Chem 2016;35:966–974. © 2015 SETAC